Pengaruh Model Problem Based Learning Terhadap Hasil Belajar Matematika Siswa - Anggriani, Putri; Amri, Mira Amelia; Siska, Maria Para (Lattice Journal : Journal of Mathematics Education and Applied, 2023)
The_low_mathematics_learning_outcomes_of class X1 Science students_at SMAN 1 Nan Sabaris are the background for conducting this research. The causal factor_is_that_students_are_not_actively involved_in_learning, so_students' problem-solving abilities do not develop well. One_model_that_can_be used_to_improve_students' mathematics learning outcomes is_by implementing a problem-based_learning model. This research aims to determine the effect of the problem based learning model on the mathematics learning outcomes of class XI IPA students at SMAN 1 Nan Sabaris. This study employs a pre-exsperimental approach utilizing a design that involves only a randomly assigned control group. The study population consisted af all eleventh-grade science students at SMAN a Nan Sabaris for the 2022/2023 academic year. Sampling used a purposive sampling technique, namely class XI IPA1 as the experimental class and class XI IPA2 as the control class. The learning outcomes analyzed are learning outcomes in the cognitive domain with multi-dimensional material. Based on data analysis, the average value obtained in the experimental class was 77.2857 and the average value in the control class was 66.3636, meaning that the average for the experimental class was higher than the control class. The results of the t-test analysis obtained tstat = 3.6566 and t(0.975; 66) = 1.998. The calculation results show that tstat > ttable means that H0 is rejected, so it can be concluded that there is an influence of learning using the problem-based learning model on the mathematics learning outcomes of Class X1 Science Students at SMAN 1 Nan Sabaris. ABSTRAKRendahnya pencapaian pembelajaran matematika siswa kelas X1 IPA SMAN 1 Nan Sabaris yang melatarbelakangi dilakukannya penelitian ini. Faktor penyebabnya adalah partisipasi siswa rendah dalam proses belajar mengajar sehingga perkembangan keterampilan menyelesaikan masalah mereka tidak optimal. Penerapan model problem based learning merupakan satu dari metode yang bisa digunakan untuk meningkatkan pencapaian pembelajaran matematika siswa. Sasaran dari penelitian ini adalah untuk mengetahui pengaruh model problem based learning terhadap hasil belajar matematika siswa. kelas XI IPA SMAN 1 Nan Sabaris. Penelitian ini merupakan pra-eksperimen dengan rancangan penelitian randomized control group only design. Subjek penelitian ini mencakup semua siswa kelas XI IPA SMAN 1 Nan Sabaris tahun pelajaran 2022/2023. Pengambilan sampel menggunakan teknik purposive sampling yaitu kelas XI IPA1 sebagai kelas eksperimen dan kelas XI IPA2 sebagai kelas kontrol. Hasil belajar yang dianalisis yaitu hasil belajar pada ranah kognitif dengan materi suku banyak.Berdasarkan analisis data, rata-rata kelas ekperimen melampaui rata-rata kelas kontrol, yaitu 66,3636 pada kelas kontrol dan 77,2857 pada kelas eksperimen. Hasil analisis uji-t diperoleh thitung = 3,6566 dan t(0,975; 66) =1,998. Hasil perhitungan terlihat thitung > ttabel berarti H0 ditolak, sehingga dapat disimpulkan bahwa terdapat pengaruh pembelajaran dengan model problem based learning terhadap hasil belajar matematika Siswa Kelas X1 IPA SMAN 1 Nan Sabaris.